1975
DOI: 10.1021/bi00674a024
|View full text |Cite
|
Sign up to set email alerts
|

Action of bacterial cytidine deaminase on 5,6-dihydrocytidine

Abstract: Cytidine deaminase from Escherichia coli was found to catalyze the hydrolytic deamination of 5,6-dihydrocytidine, at a rate slightly lower than its rate of action on the normal substrate. The results suggest that nucleophilic addition by the enzyme at the 5,6 position of the substrate is not an essential part of catalysis, unless the active site is so flexible that deamination can occur with addition in one case (cytidine) and without addition in another case (5,6-dihydrocytidine). 3,4,5,6-Tetrahydrouridine be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…(ii) Cytosines are methylated, and then some or all of these are deaminated to give thymines. On the basis of the suggestion that a suspected intermediate in the enzymatic methylation reaction is more than 10 4 times more prone to spontaneous deamination than is cytosine (11,61), we proposed that RIP may be catalyzed by a DNA methyltransferase under special conditions, such as when the methyl group donor S-adenosylmethionine is limiting (40). Supporting this model, recent studies have demonstrated that two bacterial cytosine methyltransferases can catalyze deamination (48,62).…”
Section: Rip8mentioning
confidence: 94%
“…(ii) Cytosines are methylated, and then some or all of these are deaminated to give thymines. On the basis of the suggestion that a suspected intermediate in the enzymatic methylation reaction is more than 10 4 times more prone to spontaneous deamination than is cytosine (11,61), we proposed that RIP may be catalyzed by a DNA methyltransferase under special conditions, such as when the methyl group donor S-adenosylmethionine is limiting (40). Supporting this model, recent studies have demonstrated that two bacterial cytosine methyltransferases can catalyze deamination (48,62).…”
Section: Rip8mentioning
confidence: 94%
“…The stereochemical configuration at C-4 is drawn by analogy with the observed stereochemistry at C-6 of adenosine deaminase inhibitor (Kati & Wolfenden, 1989b), but remains to be established for cytidine deaminase. Considering the ability of model nucleophiles to catalyze deamination of cytidine by adding to the 5,6-double bond (Shapiro & Klein, 1966Klein, , 1967Notari, 1967;Wechter, 1970;Wechter & Kelly, 1970;Shapiro, 1980), it seemed possible that the action of cytidine deaminase might involve addition of water or an enzyme nucleophile at the 5,6-double bond. That mechanism became less attractive when the enzyme was found to catalyze the hydrolytic deamination of 5,6-dihydrocytidine, in which 5,6-addition of a nucleophile could not occur (Evans et al, 1975). A simpler mechanism of action was suggested by the enzyme's observed sensitivity to the competitive inhibitors shown in Figure 1.…”
mentioning
confidence: 99%
“…The details of catalytic function of CDA may yield essential clues for conversion of alcohols and olefins to amines as well as in assisting asymmetric synthesis providing important alternative to conventional chemical technologies. The experimental efforts, aimed at [8][9][10]. The role of the active site residues seems to be well recognized, and the reaction energetics are supported by evidence from accurate kinetics and site-directed mutagenesis experiments [11,12].…”
Section: Introductionmentioning
confidence: 99%